Cell and Microbe Science Fair Projects Using Microscopes, Mold and More - Rainis, Kenneth G. (USA Enslow Publishers, 2005)
The simple experiments in this book will get you started learning about cells and microbes. If you are interested in competing in science fairs, this book contains lots of great suggestions and ideas for further experiments.
Include Color Illustrations and Index
Keywords: Microbiology -- Microscopy -- Biology projects